EXAMINING STUNTING INCIDENCE BASED ON MATERNAL FACTORS IN TEGAL CITY - Qudriani, Meyliya; Andari, Istiqomah Dwi; Chikmah, Adevia Maulidya; ., Taryuli (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Stunting, a condition resulting from inadequate nutrition, recurrent infections, and insufficient psychosocial stimulation, affects children's development. It is characterized by stunted growth due to nutritional deficiencies and chronic or recurring infectious diseases, indicated by a height-for-age z-score of less than -2 standard deviations. In Indonesia, the average prevalence of stunting among children under five is 30.8%. In Central Java, the prevalence is 28.5%, and in Semarang, it is 16.89%. The prevalence of stunting in Tegal City is projected to decrease by 6.7% in 2019, 4.76% in 2020, and 7.1% in 2021, reaching 16.8% from the initial value of 23.9%. This descriptive study focuses on identifying the determinants of mothers with stunted children. The study included all mothers with stunted children under five years of age in 7 villages of Tegal City, with a sample size of 27 willing participants. The findings highlight family income and maternal parity as the most dominant characteristics among the respondents. Maternal anemia, CED history, and excellent maternal knowledge level were also noted.